Development and trial of vaccines against Brucella - Lalsiamthara, Jonathan (J Vet Sci, 2017)
The search for ideal brucellosis vaccines remains active today. Currently, no licensed human or canine anti-brucellosis vaccines are available. In bovines, the most successful vaccine (S19) is only used in calves, as adult vaccination results in orchitis in male, prolonged infection, and possible abortion complications in pregnant female cattle. Another widely deployed vaccine (RB51) has a low protective efficacy. An ideal vaccine should exhibit a safe profile as well as enhance protective efficacy. However, currently available vaccines exhibit one or more major drawbacks. Smooth live attenuated vaccines suffer shortcomings such as residual virulence and serodiagnostic interference. Inactivated vaccines, in general, confer relatively low levels of protection. Recent developments to improve brucellosis vaccines include generation of knockout mutants by targeting genes involved in metabolism, virulence, and the lipopolysaccharide synthesis pathway, as well as generation of DNA vaccines, mucosal vaccines, and live vectored vaccines, have all produced varying degrees of success. Herein, we briefly review the bacteriology, pathogenesis, immunological implications, candidate vaccines, vaccinations, and models related to Brucella.